Rancang Bangun Kursi Penderita Cereblal Palsy - Arsyad, Muhammad; Anzarih, A.M. (Politeknik Negeri Ujung Pandang, 2017)
The general goal of this research is to help provide a means to train the muscles of the sufferers Cerebral Palsy (CP). In especially, the objectives are: (1) Make a seat that has a function like easy stand, (2) Provide easy stand chair at a price affordable by people suffering from CP. Problems to be solved through applied product research activities are (1) how to make a chair that has functions such as easy stand, (2) how to provide easy chair seat with low price that can be reached by CP sufferer. To achieve these goals be done designing and making a chair similar to chair easy stand for people with CP. Stages of activities include designing, manufacturing components, assembling, testing and repair. Based on the test results, it is concluded that the celebral palsi chairs function well, including the components such as knee retention, peut holder, and table. The price of one CP chair is Rp 10 million.